CURRENT ISSUES IN FOREIGN LANGUAGE TEACHING AND INNOVATIVE TECHNOLOGIES IN EDUCATION - Sabirova Nazokat Karimboyevna (Bright Mind Publishing, 2025)
This article presents the justification for using advanced technologies in foreign language teaching to enhance the quality of the learning process. It also discusses how the use of special techniques in teaching foreign language students new content can motivate actions, develop independent thinking skills, and simultaneously activate creative thinking, improving the ability to demonstrate creative abilities.
Keywords: Innovative methods, technology, competence, higher education, information technologies, foreign languages.